Comparative trichoscopic analysis of efficacy of combination therapy versus monotherapy of platelet rich plasma and topical minoxidil in the treatment of androgenetic alopecia - Annamreddy, Leepika; Kode, Sridevi; John, Akhila Merin; Rajakamal, Chinta (International Journal of Research in Dermatology, 2024)
Background: Hair is a pivotal facet of physical visage and cultural identity. Since time immemorial hair has been considered as a sign of vitality, beauty and health. Hair loss complaint is encountered by at least 50% of men and women in their lives. Androgenetic Alopecia is one of the most common causes of hair loss among youth which often leads to psychological stress. This underscores the need for early detection and treatment of androgenetic alopecia. Hence a comparative trichoscopic analysis of the efficacy of combination therapy vs monotherapy of platelet rich plasma (PRP) and topical minoxidil in the treatment of androgenetic alopecia was done. Methods: Sixty untreated cases of androgenetic alopecia were enrolled in this randomized prospective interventional study. Patients were randomly allotted into three groups. Group I (PRP with minoxidil), Group II (Minoxidil), Group III (PRP). Patients were assessed by trichoscopic evaluation, clinical photographs, physician assessment and patient self-assessment at the end of three months and six months of treatment. Results: Among group 1 (PRP+Minoxidil), a total of 55% of patients had improvement in the grade of alopecia while in group 2 (Minoxidil), 25% of patients had improvement in the grade and 40% of patients had improvement in group 3(PRP). By trichoscopic analysis, 58.6% of patients had improvement in group 1, 36.5% of patients had improvement in group 2 and 44.025% of patients improved in group 3. Conclusions: Combination therapy with both PRP+Minoxidil shows significant results when compared to individual therapies which was confirmed by trichoscopic analysis.